El telemarketing como herramienta para la comercialización de los planes de telefonía móvil, para clientes PYMES de la empresa CNT E.P en la ciudad de Guayaquil - Estrella Yunapanta, Brenda Bella (2017)
The CNT is a company that offers fixed telephony, Internet, satellite TV and mobile telephony services, but for the CNT, it is vital to reach a higher position in the mobile telephony segment through the SME segment of the city of Guayaquil. In order to reach this indicator, the company will market mobile telephony plans that are convenient for SME customers, who are mostly unaware of the fact that there are promotions and commercial benefits. In the event that the CNT does not take effective actions to publicize the promotions and benefits runs the risk of continuing to lose competitiveness in the mobile telephony sector. Therefore the implementation of an effective telemarketing program is required, having as main objective the commercial communication about the mobile promotions……..